Simplify the expression. 5.3x – 9 + 7.6x

Question

Simplify the expression.

5.3x – 9 + 7.6x

in progress 0
Thu Thủy 1 year 2021-09-04T09:51:03+00:00 2 Answers 20 views 0

Answers ( )

    0
    2021-09-04T09:52:20+00:00

    Answer:

    12.9x-9

    Step-by-step explanation:

    First you have to combine the like terms which are 5.3x + 7.6x= 12.9x. Then you just rewrite the equation 12.9x-9. You just leave the 9 by it self beacuse thers no other like terms.

    0
    2021-09-04T09:52:30+00:00

    Anwer

    12.9x−9 🙂

    5.3x+−9+7.6x

    Combine Like Terms:

    =5.3x+−9+7.6x

    =(5.3x+7.6x)+(−9)

    =12.9x+−

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )